Beyond normal central banking? Monetary policy after the pandemic - Hielke van Doorslaer; Mattias Vermeiren (European Trade Union Institute (ETUI), 2022)
In recent years the world's two largest inflation-targeting central banks - the US Federal Reserve (the Fed) and the European Central Bank (ECB) - have revised their monetary policy frameworks in a more progressive direction. Whereas the Fed decided to abandon its strategy of pre-emptive tightening whenever unemployment ran too low (implicitly acknowledging the potential benefits of 'tight labour markets' and a 'hot pressure economy' for low-income workers), the ECB became committed to better integrating climate change considerations into its monetary policy operations. In an ironic twist of fate, however, both revisions quickly became antiquated when inflation started to rise again in the wake of the pandemic. The change in macroeconomic context (from stubbornly low inflation to persistent higher inflation) led both central banks to advocate 'policy normalisation' by raising the short-term interest rates and reducing the size of the central banks' balance sheet. In this working paper we discuss the revisions of the Fed's and ECB's monetary policy frameworks and explain why a return to a pre-2008 normal central banking in response to the current inflationary crisis should not be the preferred way forward.
Keywords: 330; Geldpolitik; Inflation; Coronavirus; EU-Staaten; USA